KARAKTERISASI DAN DISTRIBUSI KELAPA MADAN DI KECAMATAN MANGGIS KABUPATEN KARANGASEM, BALI - Sumerta Yasa, I Wayan; Kriswiyanti, Eniek (SIMBIOSIS, 2016)
The purpose of research to determine themorphological characteristics and distribution of coconut variety mine in Manggis district. The research was conducted from February-March 2014 in the villageNgis, Selumbung and ApitYeh. The method used in this research is purposive sampling by observation stems ,leaves and fruit based manua lIBPGR. The result showed 18 individual coconut Madan are classified intwovarieties: a) Tall coconut (Cocos nucifera L. var. typica) 15 individual: ‘Gadang’, ‘Bingin’, ‘Bojog’, ‘Bejulit’, ‘Sudamala’, ‘Bluluk’, ‘Rangda’, ‘Naga’, ‘Bulan’, ‘Udang’, ‘Padma’, ‘Pudak Selumbung’, ‘Pudak Ngis’, ‘Mulung’, ‘Bunga’ and b) Dwarf coconut (Cocos nucifera L. var. nana) 3 individual: ‘Gading’, ‘Bulan’ dan ‘Gadang’. Distribution: in the Ngis village 15 individuals, in the Selumbung village 7 individuals and in the Apit Yeh village 5 individuals. Keywords: characterization, coconut madan, Cocos nucifera L , distribution
Keywords: characterization, coconut madan, Cocos nucifera L., distribution